The Modern VAT - Ebrill, Liam (International Monetary Fund, 2001)
Value-added tax, or VAT, first introduced less than 50 years ago, is now a pivotal component of tax systems around the world. The rapid and seemingly irresistible rise of the VAT is probably the most important tax development of the latter twentieth century, and certainly the most breathtaking. Written by a team of experts from the IMF, this book examines the remarkable spread and current reach of the innovative tax and draws lessons about the design and implementation of the VAT, as experienced by different countries around the world. How efficient is it as a tax, is it fair, and is it suitable for all countries? These are among the questions raised. This highly informative and well-researched book also looks at the likely future of the tax.